Expression of fibroblast growth factor-8 and its cognate receptors, fibroblast growth factor receptor (FGFR)-3c and-4, in fetal bovine preantral follicles - Buratini, J.; Glapinski, V. F.; Giometti, I. C.; Teixeira, A. B.; Costa, I. B.; Avellar, MCW; Barros, C. M.; Price, C. A. (Wiley-Blackwell, 2005)
Paracrine cell signaling is thought to be important for ovarian follicle development, and a role for some members of the fibroblast growth factor (FGF) family have been suggested. In the present study, we tested the hypothesis that FGF-8 and its cognate receptors (FGFR-3c and FGFR-4) are expressed in bovine preantral follicles. Reverse transcription-polymerase chain reaction was used to amplify bovine FGF-8, FGFR-3c, and FGFR-4 from preantral follicle samples and a variety of fetal and adult tissues. All three genes were widely expressed in fetal tissues, with a restricted expression pattern in adult tissues. FGF-8 and FGFR-3c were expressed in secondary follicles in 70% of fetuses examined, whereas FGFR-4 expression was significantly less frequent (20%). FGFR-3c expression frequency was significantly lower in primordial compared to secondary follicles, and FGF-8 expression showed a similar trend. FGFR-4 was only observed when all follicle classes of an individual were expressing both FGF-8 and FGFR-3c. We conclude that FGF-8 and its receptors are expressed in preantral follicles in a developmentally regulated manner. (C) 2005 Wiley-Liss, Inc.
Keywords: fibroblast growth factor-8; fibroblast growth factor receptor-3c; fibroblast growth factor receptor-4; preantral follicle; ovary